Investigation of ozone decay half-life in dependence of temperature and humidity as well as H₂S and NH₃ oxidation mechanism - Taran, V.S.; Krasnyj, V.V.; Lozina, A.S.; Chechelnitskyi, O.G.; Schebetun, A.V. (Вопросы атомной науки и техники, 2017)
In the present research, a measurement method of ozone decay half-life τ (h) in air depending on the temperature and humidity is proposed. This method allows simulating the conditions of ozone generation during sanitizing of various premises. The ozone generation was carried out in a closed volume of 0.125 m³ by ozonator based on dielectric barrier discharge. Through measurement ozone decay at temperatures of 10, 24 and 40 °C and humidity φ ~ 10, 50, 80 % was calculated. The ozone decay was found to change depending on temperature and humidity. The productivity of ARAO-1 type generator has been determined at various conditions. The H₂S and NH₃ oxidation mechanism has been studied. It was revealed that 8.6 mg of O₃ is required for of 1 mg of H₂S oxidized and 1.8 mg of ozone is required for 1 mg NH₃ oxidation.